Risk factors for dating violence among undergraduates in selected state universities in the Western Province, Sri Lanka - H. Fernando; A. Balasuriya; P. Jayawardana (College of Community Physicians of Sri Lanka, 2023)
Introduction: Dating violence (DV) is an important public health concern globally, although it has been given a low level of recognition in Sri Lanka. Objectives: To determine risk factors for DV among undergraduates in selected universities in Western Province, Sri Lanka Methods: A case control study (Phase II) was conducted as part of a large study (Phase I). Cases and controls were those with and without DV among those who reported heterosexual relationships for a duration of six months or more before the survey. Computed sample size was 200 in each group. Cases and controls were randomly selected from Phase I. Data were collected using a validated, anonymous, self-administered questionnaire. Adjusted odds ratios (AOR) were determined using multiple logistic regression. Results: Risk factors identified were female sex (AOR=2.6; 95% CI: 1.1, 6.1; p=0.03), father's low educational level (AOR=3.1; 95% CI: 1.2, 7.6; p=0.02), presence of community violence (AOR=8.5; 95% CI: 3.2, 22.2; p<0.01), watching pornography (AOR=19.8; 95% CI: 7.7, 50.8; p<0.01) and sexual abuse in childhood (AOR=22; 95% CI: 3.1, 154.8; p<0.01). Spending time with friends (AOR=0.1; 95% CI: 0.04, 0.3; p<0.01) was a protective factor. Presence of family conflicts (p=0.4), monthly income below Rs. 25000/= (p=0.4), non-engagement in extracurricular activities (p=0.4) and substance abuse of the respondents (p=0.8) were not significantly associated with dating violence. Conclusions & Recommendations: Sex, paternal education, community violence, pornography and childhood sexual abuse were the risk factors identified of DV. It is recommended to help undergraduates to handle exposure to factors in the surrounding environment which promotes development of violent ideas.